Optimización de la cuenta proveedores de la Empresa Ferreconst de la Parroquia San Juan cantón Puebloviejo, provincia de Los Ríos en el periodo 2022. - Valle Alvarado, Angelina Noralma (2023)
This case study will deal with the optimization of the suppliers account of Ferreconst Company located in the parish of San Juan del Canton Puebloviejo, it is important to emphasize that a correct optimization process within the suppliers account, improves the efficiency and profitability of any company. This account refers to the debts that the company has for the acquisition of goods or services not paid in full. Remember that it is necessary to implement rules and actions to improve the payment terms and deadlines that are foreseen within the negotiation stipulated with suppliers, in order to reduce costs and control cash flow management. The bad process or management of the products that are in stock, indirectly affect the suppliers account, although it is true that for a company to grow it must maintain a wide variety and quantity of products that meet the needs of its customers, but the unnecessary acquisition or significant economic growth of the suppliers account directly affects the profitability of the company, causing losses in its assets and capital. One of the most important alternatives to achieve a correct optimization of the suppliers account is to improve the communication and negotiation capacity with the suppliers, to establish clear payment policies that avoid delays and conflicts in the delivery of the merchandise that satisfies the company's stock.